Study of Death among Children Below Five Yearsof Age and Its Correlation with Health Care Utilization and Place of Residence. Using Verbal Autopsy as a Tool in Deharadun (Indian Journal of Forensic Medicine & Toxicology, 2020)
Children, one of the most vulnerable part of the population, face unusually high health risks as they grow.Children are the promise and future of every nation and the core of development. But it has been observedthat even after so many efforts by governments of developing countries we are far behind to achievehundred percent health care utilization by under-five population. Keeping this in view, this study wasconducted to find out any correlation in-between child mortality of under-five years of age with health careutilization and place of residence. using verbal autopsy as a tool in Dehradun.Methodology: The survey was done on all the houses of the deceased children residing in our field practiceareas by visiting their houses.Results: Among the 83 deaths reported, 38 received no treatment, 10 were treated by quakes, 19 and 16under five – children were treated in government and private hospital respectively.Conclusion: Our study shows that by utilization of health care facilities we can remarkably reduce underfive mortality.